EARLY REHABILITATION IN CRITICALLY ILL CHILDREN - ALI , S; IBRAHIM , MS; ALI , N; SHAH , SA (Biological and Clinical Sciences Research Journal, 2024)
Early rehabilitation interventions in critically ill children admitted to the Pediatric Intensive Care Unit (PICU) have shown potential to improve functional outcomes and recovery. Despite growing interest, there is limited evidence of their efficacy in pediatric populations. Objective: To evaluate the impact of early rehabilitation interventions on clinical outcomes, functional status, respiratory function, muscle strength, and quality of life in critically ill children admitted to the PICU. Methods: This randomized controlled trial was conducted in the Department of Pediatrics, Saidu Teaching Hospital, Saidu Sharif, Swat, Pakistan, from October 2023 to March 2024. A total of 230 critically ill children of both genders were enrolled and randomly assigned to two groups: Group A (n=115) received early rehabilitation interventions within 48 hours of PICU admission, and Group B (n=115) served as the control group. The primary outcomes were PICU length of stay, mortality, functional status, respiratory function, muscle strength, and quality of life. Data were analyzed using SPSS, with significance set at p<0.05. Results: The mean age of patients was 8.60±4.46 years. Group A had a shorter PICU stay (4.69±1.43 days) than Group B (5.00±1.42 days), with a significant p-value of 0.00. Mortality in Group A was 7.8% compared to 15.7% in Group B (p=0.06). Functional status improvement was higher in Group A (62.7%) versus Group B (37.3%) (p=0.00). Respiratory function improved in 73.9% of Group A versus 60.9% of Group B (p=0.03). No significant difference was found in muscle strength improvement (p=0.23). Quality of life improved significantly in Group A (51.3%) compared to Group B (28.7%) (p=0.00). Conclusion: Early rehabilitation interventions significantly improve functional outcomes, respiratory function, and quality of life in critically ill children admitted to the PICU. These findings suggest that incorporating early rehabilitation into standard PICU care may enhance recovery and reduce long-term disability in pediatric patients.